DISTANCE EDUCATION IN UKRAINE UNDER COVID-19 QUARANTINE: PROBLEMS AND NEEDS - Ivaniuk, Iryna Volodymyrivna; Ovcharuk, Oksana Vasylivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
The article considers the problems and needs of teachers during the organization of distance and blended learning in quarantine COVID-19. The paper uses and compares the results of two online surveys conducted by the authors in April 2020 and January 2021.